Dry Reforming of Methane under Mild Conditions Using Radio Frequency Plasma. Issue 5 (5th March 2020) - Devid, Edwin; Zhang, Diyu; Wang, Dongping; Ronda-Lloret, Maria; Huang, Qiang; Rothenberg, Gadi; Shiju, N. Raveendran; Kleyn, Aart W.
Abstract : Dry reforming of methane (DRM) is a challenging process wherein methane reacts with CO2 to give syngas. This reaction is strongly endothermic, typically requiring temperatures higher than 500 °C. Catalysts can be used, but the high temperatures (which are a thermodynamic requirement) often lead to catalyst deactivation. Herein, the reaction from another conceptual direction is approached, using low‐power radio frequency inductively coupled plasma (RF‐ICP). It is demonstrated that this system can give high conversions of methane and CO2 at near‐ambient temperatures. Importantly, the energy costs in this system are considerably lower compared with other plasma‐driven DRM processes. Furthermore, it is shown that the yield of hydrogen can be increased by minimizing the C2 compound formation. The factors that govern the DRM process and discuss Hα emission and its influence on H atom recycling in the process are examined. Abstract : The reaction of methane with CO2 is enhanced using radio‐frequency plasma, giving over 70% yield of syngas at 150 W and a 1:1 CO2 :methane ratio.